Sustainable environmentally-oriented development of the Ukrainian Carpathians as a key direction of the european integration progress of post-war Ukraine - Michalski, Tomasz; Radchenko, Oleksandr; Babaiev, Valerii (Theory and Practice of Public Administration, 2026)
The article presents the results of a scientific and applied analysis of the problems and prospects for sustainable environmentally-oriented development of territorial communities in the Ukrainian Carpathians in the context of decentralization, European integration, and post-war recovery. The research is conducted within the framework of deepening decentralization processes, implementing the European integration course, and addressing the needs of post-war reconstruction. The aim of the work is to generalize the current state of mountain communities, identify key constraints on their socio-economic and environmental capacity, and substantiate directions for improving local development policies through the implementation of European approaches to supporting mountain areas. It is argued that the local government reform has expanded the administrative and financial capacities of communities in the Carpathian region; however, their practical implementation is complicated by a shortage of qualified personnel, misalignment of priorities between the population and authorities, demographic and migration shifts, as well as the escalation of environmental risks exacerbated by military actions. The necessity of integrating environmental constraints and territorial potential into strategic planning processes is substantiated. This involves combining infrastructure restoration with the development of the tourism and recreation sector, supporting small and medium-sized enterprises, fostering environmental culture, and improving financial equalization tools considering the specificities of mountain areas. It is concluded that enhancing the capacity of Carpathian communities requires institutional strengthening of local governance, intensifying partnerships with EU communities, and implementing adapted European practices for supporting mountain territories. A concept of innovative environmentally oriented economic development for the Carpathian region based on digital transformation and European integration is proposed. The concept incorporates the adaptation of the European Smart Specialisation Strategy instruments to the specific conditions of the Carpathian region. The study examines the potential for developing digital employment in mountainous areas, identifying the types of employment that correspond to the region’s smart specialisation priorities. Furthermore, a cluster-based cooperative model of contract farming for the Carpathian region is proposed, highlighting the opportunities for contractual arrangements and describing the mechanism of stakeholder interaction.